The Unique Hemostatic Dysfunction in Acute Promyelocytic Leukemia - Kwaan, Hau C. (Seminars in Thrombosis and Hemostasis, 2014)
The hemostatic abnormalities seen in acute promyelocytic leukemia (APL) are unique and account for much of the morbidity and mortality of this disorder. Almost all patients present at diagnosis with laboratory findings of intravascular coagulation along with increased fibrinolysis. This unusual combination is correlated to the clinical manifestations with high risk of both bleeding and thrombosis. Recent studies have revealed that the leukemic promyelocytes in APL express increased amounts of tissue factor as well as elements of the fibrinolytic system, including tissue plasminogen activator, annexin A2, and plasminogen activator inhibitor type 1. These changes are responsive to differentiation therapy with all-trans-retinoic acid (ATRA) or with arsenic trioxide (ATO). Despite a dramatic reduction in mortality seen since the introduction of differentiation therapy with ATRA or with ATO, a large number of deaths still occur before complete remission is achieved. The early deaths are mostly attributable to the presenting coagulopathy. The prevention and management of this hemostatic abnormality have thus far been unsuccessful and remain a challenge to bring about a higher cure rate for this disease.
Keywords: acute promyelocytic leukemia; tissue factor; fibrinolysis; tPA; annexin A2